A Palestinian Discourse: Historiographic Metafiction in Rula Jebreal’s Miral - AlTaher, Bassmah (Dirasat: Human and Social Sciences, 2020)
History cannot be overlooked in fiction, and with the growing art of infusing history into the backgrounds of modern novels, Linda Hutcheon believes that history adds another dimension to various plots. Using Hutcheon’s theory of Historiographic Metafiction, this paper applies it to Rula Jebreal’s Miral. Jebreal reveals to her readers a glimpse of Palestinian life and is able to re-think patriarchal oppression and occupation from a personal point of view, and create a platform for a cultural herstory, where voices of female characters are unsilenced. Jebreal is able to transform her female characters’ lives into a historical account retold from the eyes of oppressed victims. Moreover, the film adaptation of Miral directed by Julian Schnabel is compared between plot and scenes, analyzing the purpose of each shot, role, and storyline. The comparison uses Linda Hutcheon’s Theory of Adaptation in order to clarify how author and director have attracted a much wider audience to reflect upon historical events happening in Palestine.